2005
DOI: 10.2337/diabetes.54.7.2227
|View full text |Cite
|
Sign up to set email alerts
|

Signaling Pathways Involved in Human Vascular Smooth Muscle Cell Proliferation and Matrix Metalloproteinase-2 Expression Induced by Leptin

Abstract: Accumulating evidence suggests that high concentrations of leptin observed in obesity and diabetes may contribute to their adverse effects on cardiovascular health. Metformin monotherapy is associated with reduced macrovascular complications in overweight patients with type 2 diabetes. It is uncertain whether such improvement in the cardiovascular outcome is related to specific vasculoprotective effects of this drug. In the present study, we determined the effect of leptin on human aortic smooth muscle cell (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
106
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(119 citation statements)
references
References 62 publications
9
106
0
4
Order By: Relevance
“…Esses fatores associados podem estar limitando a formação do colágeno e indiretamente protegendo a fibra muscular imobilizada (27,28) . Esse achado é extremamente importante, porém, são necessários mais estudos para determinar o mecanismo pelo qual a metformina minimizou o aumento da densidade de área do tecido conjuntivo no músculo imobilizado durante sete dias, já que tais alterações determinam a elasticidade, rigidez e extensibilidade muscular.…”
Section: Discussionunclassified
“…Esses fatores associados podem estar limitando a formação do colágeno e indiretamente protegendo a fibra muscular imobilizada (27,28) . Esse achado é extremamente importante, porém, são necessários mais estudos para determinar o mecanismo pelo qual a metformina minimizou o aumento da densidade de área do tecido conjuntivo no músculo imobilizado durante sete dias, já que tais alterações determinam a elasticidade, rigidez e extensibilidade muscular.…”
Section: Discussionunclassified
“…Leptin has been shown to enhance the proliferation of human aortic VSMCs and MMP-2 expression, with concomitant increased generation of intracellular ROS and activation of PKC, ERK1/2 and NF-κB. Metformin inhibited the ROS production and PKC, ERK1/2 and NF-κB activation (Li et al 2005). In addition, a different group showed that leptin induces hypertrophy in rat VSMCs via the p38MAPK pathway (Shin et al 2005).…”
Section: Vascular Smooth Muscle Proliferationmentioning
confidence: 99%
“…Leptin reseptörleri yapı ve fonksiyon açısından interlökin-6 gibi sitokin reseptörlerine benzemekte ve inflamasyonda rol oynamaktadırlar (28). Endoteliyal hücrelerin leptin ile uyarılması hücre içinde H 2 O 2 ve HO gibi reaktif oksijen türlerinin aşırı birikimine ve metalloproteinaz-1 ekspresyonunda artışa neden olmaktadır (29). Bu artışta leptin aracılı tirozin kinaz reseptörleri de rol oynamaktadır (30).…”
Section: Discussionunclassified